Supportive Educative in Improving the Readiness of the Anticipatory Phase of Primigravida Towards Achieving the Maternal Role - Widayati, Dhina; Susmiatin, Eko Arik; Siswoaribowo, Andika (Journal of Applied Nursing and Health, 2023)
Background: Primigravida mothers experience psychological changes, especially before delivery, related to the readiness of the anticipatory phase towards achieving the maternal role. Providing supportive education by health workers, husbands, and families can be a supporting factor in the readiness of pregnant women for the anticipatory phase. This study aims to determine the effect of supportive education on the readiness of the anticipatory phase in primigravida mothers towards achieving the role of mothers in the work area of the Pogalan Health Center, Trenggalek Regency. Methods: This research design was pre-experimental, involving 42 respondents through total sampling. The independent variable was supportive education, and the dependent variable was the readiness of the anticipatory phase towards achieving the mother's role, which is measured using a questionnaire Results: The results showed that the criteria for the readiness of the anticipatory phase before being given supportive educative intervention were mostly (66.7%) of respondents in the high category, and after the intervention, the majority (86.7%) of respondents had high readiness. Analysis with the Wilcoxon test obtained a value of = 0.008 (< 0.05), indicating a supportive educative effect on the readiness of the anticipatory phase in primigravida mothers towards the achievement of maternal roles. Conclusion: Supportive Educative can increase the mother's knowledge so that her understanding of pregnancy improves, her perception becomes positive, and she feels more confident that she is more prepared to undergo pregnancy and ready for the delivery process. Supportive education can be one method for improving the process of adaptation to the achievement of the mother's role